Case Report: Comparison of Plasma Metagenomics to Bacterial PCR in a Case of Prosthetic Valve Endocarditis - Joshua A. Lieberman; Caitlin Naureckas Li; Gabriella S. Lamb; David A. Kane; Mary K. Stewart; Ruslan A. Mamedov; Brad T. Cookson; Brad T. Cookson; Stephen J. Salipante (Frontiers Media S.A., 2021)
Molecular assays for infectious diseases have emerged as important clinical decision-making tools. Unbiased, metagenomic next-generation sequencing is a novel approach holding promise to detect pathogens missed by conventional modalities and to deconvolute admixed nucleic acid sequences from polymicrobial infections in order to identify constituent pathogens. Recent studies have raised concerns about the clinical impact of metagenomics assays and whether their expense is justified. Here, we report a case of polyclonal Streptococcus cristatus endocarditis in a 14-year-old woman with a history of Tetralogy of Fallot. Three sets of admission blood cultures and a commercial plasma metagenomics assay were negative for pathogens, despite persistent vegetations observed on the valve during a later procedure. Multiple strains of Streptococcus cristatus were identified from the explanted valve by amplicon-based 16S rRNA sequencing, confirming the patient had received appropriate antibiotic therapy. This case highlights limitations in the use and interpretation of clinical metagenomics for infectious disease diagnosis and indicates that the clinical yield of these tools may depend upon infection type and anatomic location.